Laser-induced non-equilibrium plasma kernel dynamics. (21st October 2019) - Alberti, Andrea; Munafò, Alessandro; Koll, Matthew; Nishihara, Munetake; Pantano, Carlos; Freund, Jonathan B; Elliott, Gregory S; Panesi, Marco
Abstract: A non-equilibrium model for laser generated plasmas is validated and used to investigate plasma kernel dynamics. Breakdowns in quiescent air at different ambient conditions (e.g. pressure) for different laser parameters (e.g. power density and beam wavelength) are considered. The hydrodynamics is described based on the chemically reactive Navier–Stokes equations where non-equilibrium effects are accounted for using a three-temperature model. Laser-plasma interactions over nano-second time-scales are modeled with a radiative transfer equation (RTE), including both multiphoton ionization (MPI) and inverse Bremsstrahlung (IB). Validation is conducted by comparing absorbed energy and plasma emission with the corresponding experimental measurements, and by observations of the structure of the breakdown. The laser generated plasma exhibits a two-lobe structure, developing both in the forward and backward directions. An analysis of the dynamics suggests that the kernel evolution results from a radiation-driven wave that is: (i) triggered by MPI, (ii) sustained by energy deposition in IB interactions, which compensates for the energy lost by free-electrons in ionizing collisions, and (iii) guided by both MPI and ionization by electron impact (IE).